Autoantibodies in Patients With Immune-Related Adverse Events From Checkpoint Inhibitors: A Systematic Literature Review. Issue 2 (9th March 2022) - Ghosh, Nilasha; Chan, Karmela K.; Jivanelli, Bridget; Bass, Anne R.
Abstract : Background: Immune-related adverse events (irAEs) from immune checkpoint inhibitors (ICIs) are sometimes associated with autoantibodies, but we do not know how frequently or whether these autoantibodies are present before ICI initiation. Our aim was to determine the positivity rate of autoantibodies in patients with organ-specific ICI-associated irAEs and determine their value as pretreatment biomarkers. Methods: We searched for all English, peer-reviewed publications from MEDLINE, Embase, and Cochrane Library through February 20, 2020, and included any publication describing patients with irAEs and reporting results of any autoantibody investigation. Three reviewers independently extracted data, and 1 reviewer verified all data for accuracy and quality of reporting. Results: We identified 515 publications. Most reports described endocrine, rheumatic, gastrointestinal/hepatic, and myositis/myasthenia/myocarditis irAEs. Autoantibodies were present in close to 50% of patients with ICI-associated endocrinopathies. Anti-BP180 was found in more than 50% of patients with skin irAEs. Antibodies were also common in patients with the triad of myositis/myasthenia/myocarditis including striational antibodies (49%), acetylcholine receptor antibodies (40%), and myositis-associated antibodies (27%). Only 11% of patients with arthritis had either rheumatoid factor or cyclic citrullinated peptide antibodies, and only 30% of patients with sicca had Sjögren antibodies. Autoantibodies were also relatively uncommon in patients with hepatitis (antinuclear antibody, 18%) and colitis (perinuclear antineutrophil cytoplasmic antibody, 19%). Some cohort studies analyzing pre-ICI seropositivity suggest there may be a role for autoantibodies as biomarkers of irAEs. Conclusions: Reported autoantibody positivity is high in irAEs involving the endocrine organs, skin, and muscle, but lower in irAEs affecting other organ systems. Autoantibody investigations in pre-ICI treatment patients have yielded mixed results regarding their utility as a biomarker of irAEs.